Inhibition of anammox activity by phenol: Suppression effect, community analysis and mechanism simulation. (July 2019) - Lyu, Liting; Zhang, Kuo; Li, Zijun; Ma, Yongguang; Chai, Tianyu; Pan, Yuan; Wang, Xiaoning; Li, Songlin; Zhu, Tong
Abstract: Anammox is a distinctive bacterium that is extremely sensitive to and inhibited by organic matter. This weakness becomes a limiting factor for the application of anammox to treat wastewater especially that the underlying mechanisms in the inhibition of phenol remain unclear. In this study, phenol was chosen to determine the possible factors leading to the inhibition of anammox through community variation and molecular simulations. Results of the short-time batch experiment showed that 400 mg L −1 or 1000 mg L −1 of phenol immediately inhibited the anammox activity. Profiles from 16S rRNA sequences showed that the community structures remained unchanged during the first four hours. Molecular simulation between phenol and the key enzyme hydrazine synthase (HZS) showed that phenol combined with HZS and even had the ability to competitively bind with HZSα-haem αI and HZSγ-haem γI sites. Highlights: Phenol have immediate inhibition on Anammox activity. Community analysis of the incubated Anammox sludge has been expanded. Molecular simulation infers that phenol block the synthesis of hydrazine at the key enzyme in anammoxosome. This study gives a new idea to overcome the organic (especially phenol) inhibition on Anammox.